Child-Perpetrated Family Violence in Kinship Care in Victoria. (26th June 2018) - Breman, Rachel; MacRae, Ann; Vicary, Dave
Abstract : There is growing evidence to support our understanding of adolescent violence in the home, however, there is a paucity of research about child-perpetrated violence that occurs within the context of kinship care. In 2017, Baptcare commenced research with 101 kinship carers in Victoria to gain a better understanding of how family violence was impacting on children and families. This research included a focus on child-perpetrated violence directed towards carers once the kinship placement commenced. In this context, family violence means any act of physical violence, emotional/psychological violence, verbal abuse and property damage caused by the child. This study utilised an online survey and semi-structured interviews that specifically targeted kinship carers who had direct experience of family violence. Findings demonstrated the disturbing types of child-perpetrated violent and aggressive behaviours kinship carers experienced. The data indicates that incidents of violence occurred early in the placement, they occurred frequently, and carers experienced multiple acts of violence from the child. The impact of the violence on the carer's household is significant in terms of the carer's health, wellbeing and placement stability. Further, the findings highlight the transgenerational nature of family violence in the context of kinship care in Victoria. The study described in this paper is the first step in understanding and exposing this complex issue and draws attention to some of the significant issues confronting Victorian kinship families experiencing family violence. This paper will describe the approach that Baptcare is taking to address family violence in its kinship-care programs.